ART, TEACHING ACTIVITY AND THE DEVELOPMENT OF CREATIVE CAPACITY IN SCHOOL EDUCATION - Abreu, Thiago Xavier de [UNESP] (Univ Estadual Sudoeste Bahia, 2019)
Review of the Creativity in art and school education: a contribution to Historical Critical Pedagogy in the light of Georg Lukacs and Lev Vigotski, by Maria Claudia da Silva Saccomani.
Keywords: Art; Creativity; School education